Antiretrovirals for Primary HIV Prevention: The Current Status of Pre- and Post-Exposure Prophylaxis - Krakower, Douglas S. (Curr HIV/AIDS Rep, 2015)
In light of the 2 million HIV infections that occur globally each year, there is a need to optimize strategies that integrate biomedical and behavioral approaches to HIV prevention. Post-exposure prophylaxis (PEP) immediately after acute high-risk exposures and pre-exposure prophylaxis (PrEP) for those who engage in recurrent high-risk behaviors are promising bio-behavioral approaches to decreasing HIV transmission. Guidelines have recommended PEP for occupational and non-occupational exposures for over 15 years, but uptake of PEP has been limited, partly as a result of insufficient awareness of this intervention among persons at highest risk for acquiring HIV. However, since the publication of large randomized clinical trials demonstrating the efficacy of PrEP, and the dissemination of guidelines endorsing its use, there is a renewed focus on bio-behavioral prevention. Numerous studies have recently assessed the acceptability of bio-behavioral prevention programs among diverse populations or described experiences implementing these programs in “real-world” settings. As research and clinical data informing optimal utilization of PEP and PrEP are rapidly accumulating, this review provides a timely summary of recent progress in bio-behavioral prevention. By contextualizing the most noteworthy recent findings regarding PEP and PrEP, this review seeks to inform successful implementation of these promising prevention approaches.